Assessing the effect of supply chain management practices on the operational performance of ghana rubber estates limited: the mediating role of knowledge sharing. - ADJAKLO GODWIN EDEM (KNUST, 2024)
A thesis submitted to the institute of distance learning, Kwame Nkrumah university of science and technology, in partial fulfilment of the requirement for the degree masters of science in logistics and supply chain management institute of distance learning, kunst